The Role of Land Deed Making Officials (PPAT) in Making Deeds of Land Use Rights by Foreign Citizens - Ayuningtyas, Septia Nova (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2022)
The aims of this study are to analyze: 1) The juridical implications of the ownership of land rights for foreign citizens in the concept of legal certainty. 2) The role of the Land Deed Making Officer (PPAT) in making deed of land use rights by foreign nationals. The approach method used in this research is an empirical juridical approach. The specification of the research used is descriptive analytical research. Types of data using primary data and secondary data with literature and interview collection methods. The data analysis method used in this research is qualitative analysis. Research results: 1) The juridical implications for the ownership of land rights for foreign citizens in the concept of legal certainty are guaranteed by laws and regulations. Legal foreigners have rights to land with the status of ownership rights, as well as guarantees of legal certainty regarding the permissibility of foreigners to own land with the status of usufructuary rights, as explained in Article 42 of the UUPA. The period of ownership of usufructuary rights is regulated in Article 52 of Government Regulation of the Republic of Indonesia Number 18 of 2021 that usufructuary rights over State Land and Land of Management rights with a period granted for a maximum period of 30 years are extended for a maximum period of 20 years, and renewed for maximum term of 30 years. 2) The role of the Land Deed Making Officer (PPAT) in making land use rights deeds by foreign nationals is to make agreements for granting usage rights over ownership rights. Before making the deed, the PPAT must ensure that the parties have fulfilled the requirements in the Laws and Regulations.Keywords: Citizen; Foreign; Rights.